Gaps in Accessibility of Pediatric Formulations: A Cross-Sectional Observational Study of a Teaching Hospital in Northern Thailand - Prangthong Tiengkate; Marc Lallemant; Pimlak Charoenkwan; Chaisiri Angkurawaranon; Penkarn Kanjanarat; Puckwipa Suwannaprom; Phetlada Borriharn (MDPI AG, 2022)
The lack of appropriate medicines for children has a significant impact on health care practices in various countries around the world, including Thailand. The unavailability of pediatric medicines in hospital formularies causes issues regarding off-label use and extemporaneous preparation, resulting in safety and quality risks relating to the use of medicines among children. This research aimed to identify missing pediatric formulations based on the experience of healthcare professionals in a teaching hospital in northern Thailand. A cross-sectional survey was conducted to collect data on missing pediatric formulations, the reasons for their inaccessibility, their off-label uses, their reactions to the situation, and suggestions to improve access to these identified medications. The survey was distributed to all physicians, nurses, and pharmacists involved in prescribing, preparing, dispensing, and administering pediatric medicines. A total of 218 subjects responded to the survey. Omeprazole, sildenafil, and spironolactone suspension were most often identified as missing formulations for children by physicians and pharmacists. They are unavailable on the Thai market or in any hospital formulary. For nurses, sodium bicarbonate, potassium chloride, and chloral hydrate were the most problematic formulations in terms of preparation, acceptability, and administration. These medicines were difficult to swallow because of their taste or texture.